Perlindunganhukum Bagi Nasabah Atas Lelang Eksekusi Terhadap Barang Jaminan Hak Tanggungan - Sudiarto Sudiarto; Muhammad Arba; Lalu Muhammad Hayyan Ul Haq (Commerce Law, 2023)
This study aims to analyze the occurrence of an execution auction of collateralized mortgages unilaterally, to analyze the procedures and implementation of execution auctions, and to analyze legal protection for customers over auctions of mortgaged collateral. The approach methods used in this research are the legal approach (statue approach), the conceptual approach (conspetual approach). data collection techniques using document study techniques, observation and interview techniques. Whereas the factors that led to the occurrence of a unilateral auction were because one of the parties defaulted on the agreed agreement. The factors that cause default are divided into two, namely, the first is internal factors and external factors. That the Mortgage Execution Auction Procedure consists of 3 procedures, namely the Pre Auction Procedure, the Auction Implementation Procedure, and the Minutes of Auction. That legal protection is divided into repressive legal protection and preventive legal protection. In the auction of the object of guarantee of Mortgage, the Bank has not provided protection to customers. When the auction offer for the object of the Guaranteed Mortgage is approved by the KPKNL, the Bank makes an announcement of the auction and in the bid offer that the object of the Guaranteed Guarantee will be auctioned, the customer can obtain legal protection against the losses he receives on the Mortgage which is offered at a price far from fair and reasonable value